2007
DOI: 10.1029/2007gl031797
|View full text |Cite
|
Sign up to set email alerts
|

UK peatland streams release old carbon dioxide to the atmosphere and young dissolved organic carbon to rivers

Abstract: Since the end of the last ice age, sequestration and storage of CO2 from the atmosphere by peatlands in the northern hemisphere has produced a terrestrial C pool of comparable magnitude to that of the global atmosphere. Destabilisation of the peatland C pool will have significant positive climate change feedbacks both directly (via the atmospheric pathway) and indirectly (via the aquatic pathway). Streams and rivers draining peatlands are supersaturated with CO2 and contain high concentrations of dissolved org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
76
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 32 publications
(53 reference statements)
14
76
1
Order By: Relevance
“…Measurements of DOC-14 C from UK peat catchments suggest that the majority is derived from recently fixed plant material rather than older peat (C. D. . On the other hand, 14 C measurements of evaded CO 2 suggest that significantly older C is being released in some peatland streams, some of which may be geogenic rather than biogenic in origin (Billett et al 2007). …”
Section: Historical Rates Of C Accumulationmentioning
confidence: 99%
“…Measurements of DOC-14 C from UK peat catchments suggest that the majority is derived from recently fixed plant material rather than older peat (C. D. . On the other hand, 14 C measurements of evaded CO 2 suggest that significantly older C is being released in some peatland streams, some of which may be geogenic rather than biogenic in origin (Billett et al 2007). …”
Section: Historical Rates Of C Accumulationmentioning
confidence: 99%
“…Diurnal fluorescence cycles in a Californian agricultural stream (Spencer et al 2007) suggest significant DOC processing over short time periods. Billett et al (2007) and Billett and Moore (2008) have shown that peat headwater streams are hotspots for CO 2 release. The recognition of the relative lability of dissolved organic matter in freshwater systems has therefore led to the increased interest in the use of radiocarbon analyses to understand the relative age and processing of DOC (Evans et al 2007;Tipping et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Time-concentration changes (Figs 1 240 and 2) confirm that the build-up of CO 2 and CH 4 concentrations within the chambers was mostly linear and typical of diffusive emissions (Hornibrook 2009). In contrast, ebullition 242 events produce more temporally and spatially variable gas concentrations in collection chambers (Hornibrook 2009;Walter et al 2006Walter et al , 2008 (Billett et al 2006(Billett et al , 2007. CH 4 emitted by ebullition 330 from tundra and boreal lakes (Walter et al 2008) and Siberian thaw lakes (Walter et al 2006) has been reported to have considerably wider ranges in 14 C age, from > 40 000 years BP to 332 modern (e.g.…”
mentioning
confidence: 99%
“…Mayorga et al 2005). Studies applying these techniques have shown that evaded CO 2 can vary considerably in age, ranging 58 from a few years for CO 2 degassing from Amazonian rivers (Mayorga et al 2005), to over 1000 years BP for some UK peatland streams (Billett et al 2006(Billett et al , 2007.…”
mentioning
confidence: 99%
See 1 more Smart Citation